1997
DOI: 10.1074/jbc.272.9.5533
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Bacterial Toxin Affinity and Specificity for Glycolipid Receptors by Surface Plasmon Resonance

Abstract: The primary virulence factors of many pathogenic bacteria are secreted protein toxins which bind to glycolipid receptors on host cell surfaces. The binding specificities of three such toxins for different glycolipids, mainly from the ganglioside series, were determined by surface plasmon resonance (SPR) using a liposome capture method. Unlike microtiter plate and thin layer chromatography overlay assays, the SPR/liposome methodology allows for real time analysis of toxin binding under conditions that mimic the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
195
5

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(209 citation statements)
references
References 33 publications
9
195
5
Order By: Relevance
“…Binding to the Supported Planar Bilayers-Membrane binding of tryptophan mutants was also checked by SPR, an increasingly popular technique for measuring protein-membrane interactions. Usually immobilized lipid vesicles or bilayers formed on a hydrophobic surface are used (42)(43)(44)(45). We have chosen a membrane bilayer tethered to the gold chip by thiolipids ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Binding to the Supported Planar Bilayers-Membrane binding of tryptophan mutants was also checked by SPR, an increasingly popular technique for measuring protein-membrane interactions. Usually immobilized lipid vesicles or bilayers formed on a hydrophobic surface are used (42)(43)(44)(45). We have chosen a membrane bilayer tethered to the gold chip by thiolipids ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Gal␤3GalNAc disaccharide moiety is necessary for binding (10,11). Recent studies using surface plasmon resonance to study binding of purified H C fragment have extended these findings and demonstrated a preference for GD1b over GT1b and negligible binding to GQ1b gangliosides (12).…”
mentioning
confidence: 75%
“…Study of macromolecule-ligand interaction by SPR method depends solely on the mass changes during the reaction (18,19). Additionally, in SPR the ability to form model membrane assemblies, monolayers, or bilayers incorporating the biologic receptors which mimic the natural environment offer additional opportunities to study, in molecular terms, the surfaceassociated phenomena.…”
Section: Resultsmentioning
confidence: 99%